Women Architects and Social Housing in the Basque Country (1978-2008). An Approach from a Feminist Perspective - Olatz Ocerin-Ibáñez; Itziar Rodríguez-Oyarbide (Feminismo/s)
This article addresses the presence of women architects in social housing in the Basque Country between 1978 and 2008 from a feminist perspective. To this end, the first section of the paper is devoted to the figure of the architect Margarita Mendizábal, in order to display the unequal and male-dominated professional context that the Basque architect found after her graduation in 1956. In 1978, after two decades in the profession, Mendizábal designed a project to build a hundred social housing units in Madrid, in fact, the largest social housing project that she developed during her professional career. Until the early seventies there is no woman working as freelance architect in the Basque Country. In 1977, the School of Architecture of the UPV/EHU (University of the Basque Country) was created; this fact worked as an activating agent for the presence of women architects after the beginning of the nineties. In this regard, the last section of this article provides statistical data to quantify the presence of women architects in the Basque Country. This data gathers information related to women architects teaching at the School of Architecture of the UPV/EHU, in the professional sphere as freelance architects belonging to the Basque-Navarre Architects Association (COAVN) and, finally, in designing social housing developed by the Basque Government after taking over this area in 1981. The quantification of women out of total social housing developments shows that there are many fewer female than male architects working in this field. Furthermore, we provide a series of social housing cases authored or co-authored by women architects that show a relevant contribution to architecture and architectural culture in the Basque Country.